Wykorzystanie stochastycznych modeli umieralności do budowy dynamicznych tablic trwania życia - Papież, Monika (The Application of Stochastic Mortality Models for Building of Projected Mortality Tables, 2008)
The paper examines the usefulness of stochastic mortality models in estimating the values in the dynamic mortality tables which take into account rising life expectancy. Because parameter estimation is done on the basis of historical data, and it is not possible to obtain complete projected mortality tables for Poland from the period 1955-2005, that is why the analysis will be carried out for Slovakia, Czech Republic and Hungary. And because Poland is characterised by similar dynamics of changes to the above mentioned Central European countries, it will be justifiable to draw conclusions regarding also this country. Forecasts are made for selected countries on the basis of estimated values of the parameter in the period 1955-1995. For modelling and forecasting time series/mortality trends the ARIMA models will be used.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 18, s. 79-87